Crystallization-Enhanced Emission and Room-Temperature Phosphorescence of Cyclic Triimidazole-Monohexyl Thiophene Derivatives - Daniele Malpicci; Alessandra Forni; Elena Cariati; Riku Inoguchi; Daniele Marinotto; Daniele Maver; Federico Turco; Elena Lucenti (Molecules, 2022)
The development of organic room-temperature phosphorescent (ORTP) materials represents an active field of research due to their significant advantages with respect to their organometallic counterparts. Two cyclic triimidazole (TT) derivatives bearing one and three hexyl-thiophene moieties, TT-HThio and TT-(HThio)3, have been prepared and characterized. Both compounds display enhanced quantum yields in their crystalline form with respect to those in a solution state, revealing crystallization-enhanced emissive (CEE) behavior. Importantly, while single fluorescence is observed in solution, crystalline powders also feature dual ORTP, whose respective molecular and aggregate origins have been disclosed through X-ray diffraction analysis and DFT/TDDFT calculations. The relation between the photophysical properties of TT-HThio and its crystallinity degree has been confirmed by a decrease in photoluminescent quantum yield (Φ) and loss of vibronic resolution when its crystals are ground in a mortar, revealing mechanochromic behavior and confirming CEE features.